Minimal Art : a Critical Anthology - Flavin, Dan (New York : E.P. Dutton & Co, Inc. New York, 1968)
Agam, Yaacov ; Agostini, Peter ; Ahlander, Leslie Judd ; Albers, Josef ; Alloway, Lawrence ; Anastasi, William ; Andre, Carl ; Annesley, David ; Antonakos, Stephen ; Anuszkiewicz, Richard ; Apple, Billy ; Arp, Hans (Jean) ; Artschwager, Richard ; Ashbery, John ; Ashton, Dore ; Aubertin, Bernard ; Baer, Jo ; Baker, Elizabeth ; Balla, Giacomo ; Balthus ; Bannard, Darby ; Baranov-Rossiné, W. ; Bardo, Arthur ; Baringer, Richard ; Barry, Robert ; Bart, Robert ; Battcock, Gregory ; Bell, Larry ; Belloli, Carlo ; Benedikt, Michael ; Bengston, Billy ; Bennett, John F. ; Benton, Fletcher ; Berlant, Tony ; Bernhouse, Donald ; Bill, Max ; Bishop, James ; Bladen, Ronald ; Boccioni, Umberto ; Bochner, Mel ; Bolus, Michael ; Bonnard, Pierre ; Bontecou, Lee ; Boriani, Davide ; Boto, Martha ; Bourdon, David ; Brancusi, Constantin ; Braque, Georges ; Breer, Robert ; Brett, Guy ; Breuer, Marcel ; Bridgman, P.W. ; Bronzino, Agnolo ; Brunelle, Al ; Bury, Pol ; Cadoo, Emil ; Cage, John ; Calas, Nicolas ; Calder, Alexander ; Cambillo, Maria Trudi ; Canova, Antonio ; Caro, Anthony ; Carrieri, Raffaele ; Carrà, Carlo ; Castel, Louis Bertrand ; Cavell, Stanley ; Chamberlain, John ; Christo ; Chryssa ; Clay, Jean ; Coates, Robert ; Colombo, Gianni ; Colt, Priscilla ; Coplans, John ; Cornell, Joseph ; Cote, Alan ; Crampton, Rollin ; Cézanne, Paul ; D'Arcangelo, Allan ; Dali, Salvador ; Darboven, Hanne ; David, Jacques Louis ; David, Ronald ; Davis, Gene ; Davis, Stuart ; De Chirico, Giorgio ; De Kooning, Elaine ; Decker, Lindsey ; Degas, Edgar ; Delacroix, Eugène ; Delap, Tony ; Depero, Fortunato ; Dine, Jim ; Dorfles, Gillo ; Dougherty, Frazer ; Dove, Arthur ; Downing, Thomas ; Doyle, Tom ; Duchamp, Marcel ; Duran, Robert ; Ernst, Max ; Evans, Jan ; Feeley, Paul ; Ferber, Herbert ; etc.
2 ex.
Engels
boek